Feminism Paradigm In Gender Equality Argument of Nasaruddin Umar - Fata, Ahmad Khoirul; Iderus, Muhammad Hasan Said (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
The idea of gender equality, that dominates contemporary men-women relation discourse, makes a number of Muslim thinkers trying to reinterpretation some of the religious doctrines that are considered as biased. At this point the scripture became the main target of the review, because of its position as a major source of religious doctrines. This effort has been done by Nasaruddin Umar through the book